A unique junctional palindromic sequence in mitochondrial DNA from a patient with progressive external ophthalmoplegia. Issue 6 (1st December 2000) - Saiwaki, T; Shiga, K; Fukuyama, R; Tsutsumi, Y; Fushiki, S
Abstract : A polymerase chain reaction (PCR) based procedure was modified to determine the deletion of mitochondrial DNA (mtDNA). The protocol consists of coamplification both of deleted and wild-type segments of mtDNA using a long PCR technique; evaluation of the deleted portion within the amplified DNA segments by restriction enzyme digestion followed by densitometrical analysis; and direct subcloning into a plasmid vector for DNA sequencing. The procedure revealed a 5.3 kb deletion of mtDNA in the biopsied muscle tissue obtained from a patient clinically diagnosed with progressive external ophthalmoplegia. The 5′ and 3′ sequences at both sides of the breakpoint comprise a 17 bp palindrome and 5 bp tandem repeats, suggesting that the deletion might occur through slipped mispairing and other novel mechanisms. This improved procedure has the potential to detect deletions occurring in the entire length of mtDNA, and mighty be useful for clinical screening of progressive external ophthalmoplegia.